Internalization of Dance Art Activities to Improve Self-Confidence in Early Childhood - Anggun, Aluf Wahdati; Novaliana, Fitri Ayu; Sholihah, Imro’atus; Usriyah, Lailatul (JOYCED: Journal of Early Childhood Education, 2026)
Purpose - This study investigates how structured dance activities contribute to the development and internalization of self-confidence in early childhood. While previous studies have highlighted the benefits of dance for cognitive, social-emotional, and motor development, limited attention has been given to how artistic experiences become internalized as enduring self-confidence. This study integrates perspectives of self-efficacy, social learning, experiential learning, and internalization to explain this process. Design/methods/approach - a qualitative approach was conducted at RA Mabdaul Ulum Rowosari, Sumberjambe District, Jember Regency, East Java, Indonesia. Participants included 20 children aged 4–6 years, four teachers, and ten parents. Data were collected through structured observations, semi-structured interviews, teachers’ reflective journals, and documentation, then analyzed using thematic analysis. Findings - Children’s self-confidence developed progressively through repeated participation in structured dance activities. Children became more willing to perform in front of others, demonstrated better emotional regulation, engaged more actively in social interactions, and expressed greater confidence in sharing ideas and completing tasks. Four major themes emerged: confidence in public performance, emotional expression, social cooperation, and the internalization of self-beliefs through artistic experiences. These findings suggest that dance serves not only as an artistic activity but also as an experiential learning process that helps children develop positive perceptions of their abilities. Research implications/limitations - The study contributes theoretically by providing a conceptual explanation of how self-confidence is internalized through artistic experiences, extending existing research beyond outcome-focused evaluations of dance. Originality/value - Practically, the findings support the integration of dance into early childhood curricula as an arts-based strategy to foster self-confidence and holistic child development. Future research should examine the long-term effects of dance interventions in diverse educational and cultural settings.